Thymoquinone and aerobic exercise mitigate HFpEF-induced cardiac injury via Apaf1/Cycs axis regulation - Pei, Zuowei; Gao, Shan; Yang, Jin; Liu, Chang; Pan, Yanyan (Frontiers in Pharmacology, 2025)
IntroductionHeart failure with preserved ejection fraction (HFpEF) is a prevalent clinical syndrome associated with high morbidity and mortality. Oxidative stress, apoptosis, and fibrosis are central to its pathophysiology. This study aimed to investigate the synergistic cardioprotective effects of thymoquinone (TQ) and aerobic exercise, with a particular focus on the Apaf1/Cycs-mediated apoptotic pathway.MethodsMale C57BL/6J mice were randomly assigned to five groups: Control, HFpEF, HFpEF + TQ, HFpEF + exercise, and HFpEF + TQ + exercise. HFpEF was induced by a high-fat diet combined with Nω-Nitro-L-arginine methyl ester (L-NAME) administration for 10 weeks. TQ (50 mg/kg/day) and aerobic exercise (60% of maximal velocity, 5 days/week for 12 weeks) were applied as interventions. In vitro HFpEF models were established in H9c2 cardiomyoblast cells treated with L-NAME. Histological and molecular changes were assessed by immunofluorescence, co-immunoprecipitation, and TUNEL assays.ResultsThe combined treatment of TQ and aerobic exercise significantly reduced myocardial fibrosis, apoptosis, and oxidative stress compared with either intervention alone. Mechanistically, the combination downregulated the interaction between Apaf1 and Cycs, thereby suppressing cardiomyocyte apoptosis.DiscussionThese findings demonstrate that TQ and aerobic exercise exert synergistic cardioprotective effects in HFpEF by attenuating oxidative stress, fibrosis, and apoptosis through inhibition of the Apaf1/Cycs apoptotic pathway. The results provide new insights into adjunctive therapeutic strategies for HFpEF management.